2010
DOI: 10.1038/tpj.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms C677T and A1298C in the MTHFR gene in Mexican patients with rheumatoid arthritis treated with methotrexate: implication with elevation of transaminases

Abstract: Rheumatoid arthritis (RA) is the prototype of the rheumatic diseases worldwide. Methotrexate (MTX) is the drug of first choice in the treatment of this disease due to its immunosuppressant effect. However, side events are present in 30% of the patients. The C677T and A1298C polymorphisms of the methylenetetrahydrofolate reductase (MTHFR) gene are involved in the metabolism of MTX. Earlier studies reported an association between these polymorphisms and elevation of hepatic enzymes. We analyzed the frequencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
1
28
1
3
Order By: Relevance
“…There was reduced heterogeneity detected for the toxicity studies among the five pooled Caucasian studies 19,24,28,53 (I 2 ¼ 51.1% P ¼ 0.08), but the mean effect across studies suggested no association with toxicity (OR ¼ 1.12 95% CI ¼ 0.69-1.82). Significant heterogeneity remained between the eight studies restricted to nonCaucasian populations 18,20,22,23,[25][26][27]54 (I 2 ¼ 74.62% Po0.001) but again, no association with toxicity was detected (OR ¼ 1.56 95% CI ¼ 0.83-2.93).…”
Section: Meta-analysis Of Mthfr C677t Efficacy and Toxicitymentioning
confidence: 95%
See 4 more Smart Citations
“…There was reduced heterogeneity detected for the toxicity studies among the five pooled Caucasian studies 19,24,28,53 (I 2 ¼ 51.1% P ¼ 0.08), but the mean effect across studies suggested no association with toxicity (OR ¼ 1.12 95% CI ¼ 0.69-1.82). Significant heterogeneity remained between the eight studies restricted to nonCaucasian populations 18,20,22,23,[25][26][27]54 (I 2 ¼ 74.62% Po0.001) but again, no association with toxicity was detected (OR ¼ 1.56 95% CI ¼ 0.83-2.93).…”
Section: Meta-analysis Of Mthfr C677t Efficacy and Toxicitymentioning
confidence: 95%
“…Significant heterogeneity remained between the four studies restricted to non-Caucasian populations 18,20,26,27 (I 2 ¼ 60.4% P ¼ 0.05) but again, on average there was no association with efficacy detected (OR ¼ 0.63 95% CI 0.30-1.33) (Figure 3). In terms of toxicity outcomes the heterogeneity was moderate, albeit nonsignificant for both Caucasian (I 2 ¼ 43.5% P ¼ 0.13) 32,53 and non-Caucasian (I 2 ¼ 59.2% P ¼ 0.086) 18,20,25,27,54 populations and the mean effect across studies for both Caucasian (OR ¼ 1.49 95% CI 0.84-2.62) and non-Caucasian (OR ¼ 0.98 95% CI 0.57 -1.70) populations was not statistically significant ( Figure 4). Meta-regression results did not suggest a significant association between the effect size and the study co-variates tested (data not shown).…”
Section: Meta-analysis Of Mthfr A1298c Efficacy and Toxicitymentioning
confidence: 98%
See 3 more Smart Citations